A high-strength aerosol can bottom cover material and preparation method thereof
By using aluminum alloy materials of specific components and performing microarc oxidation treatment, a dense protective film is formed, the problem of insufficient strength of the aerosol can bottom cover material is solved, high strength and corrosion resistance are improved, and the application scope is expanded.
Patent Information
- Application Number
- CN202510049840.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-04
AI Technical Summary
The strength performance of existing aerosol can bottom cover materials is relatively weak, limiting its application range.
Aluminum alloy material with specific components is used, and a dense protective film is formed by microarc oxidation treatment, including the addition of zinc and titanium in the same proportion and the use of modification enhancer, combined with microarc oxidation treatment to improve the strength and corrosion resistance of the material.
It significantly improves the strength and corrosion resistance of the aerosol can bottom cover material, broadens its application field, and has good insulation and heat impact resistance.
Smart Images

Figure CN119753451A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerosol can bottom cover materials, in particular to a high-strength aerosol can bottom cover material. Background Art
[0002] Aerosol cans are pressurized containers used to hold products that can be sprayed or dispensed in the form of a fine mist or spray using a propellant. They usually consist of a metal can (such as an aluminum can) or container, a valve system, a propellant, and the product to be dispensed.
[0003] In terms of personal care, aerosol cans are widely used in cosmetics and daily care products, including: perfume: provides long-lasting fragrance, easy to carry and use; hair styling products such as hair spray and mousse: help users easily create their ideal hairstyle; antiperspirants and deodorants: keep the body dry and comfortable, and avoid embarrassing odors; facial cosmetics: such as toner, spray foundation, etc., are easy to apply evenly and touch up; hair dyes: simplify the hair dyeing process and make the color more even and lasting.
[0004] Aerosol cans are also used in the following industries:
[0005] Medical field: preparation of drug samples, drug sprays, oral sprays, etc.
[0006] Food industry: used for food packaging and spraying, such as seasonings, preservatives, etc.
[0007] Agriculture: As a carrier of pesticides, it enables precise application of pesticides.
[0008] Laboratory: used to store and transport experimental reagents.
[0009] It can be seen that aerosol cans have a wide range of applications. However, the strength performance of existing aerosol can bottom cover materials is relatively weak, resulting in certain limitations on their application.
[0010] Based on this, a high-strength aerosol can bottom cover material is provided to solve the existing technical problems. Summary of the invention
[0011] The purpose of the present invention is to provide a high-strength aerosol can bottom cover material and a preparation method thereof, so as to solve the deficiencies in the prior art.
[0012] The technical solution adopted by the present invention is as follows:
[0013] A high-strength aerosol can bottom cover material, comprising the following components by mass fraction:
[0014] Si 6.5-7.1%, Mg 0.22-0.30%, Cu 0.1-0.2%, Zn 0.5-0.1%, Ti 0.5-0.1%, Ni ≤ 0.1%, Fe ≤ 0.1%, Pb ≤ 0.003%, Sn ≤ 0.003%, the balance is Al;
[0015] The high-strength aerosol can bottom cover material is subjected to micro-arc oxidation treatment.
[0016] As a further technical solution, the mass ratio of Zn to Ti is 1:1.
[0017] As a further technical solution, the Ni mass fraction is greater than the Fe mass fraction.
[0018] As a further technical solution, the electrolyte composition used in the micro-arc oxidation treatment includes:
[0019] Modifier and enhancer 1.0-1.5g / L, sodium silicate 10-16g / L, sodium phosphate 10-16g / L, sodium metavanadate 1-2g / L, potassium titanium oxalate 0.1-0.2g / L, and the rest is water.
[0020] As a further technical solution: the mixing mass ratio of the sodium metavanadate and potassium titanium oxalate is 10:1.
[0021] As a further technical solution, the preparation method of the modified reinforcing agent is:
[0022] First, add the complexing agent to the nitric acid solution, adjust the temperature to 40°C, and stir for 30 minutes to obtain a first mixed solution;
[0023] Wherein, the complexing agent is aminocarboxylic acid;
[0024] Among them, the mass concentration of nitric acid solution is 0.35mol / L;
[0025] The mass ratio of the complexing agent to the nitric acid solution is 1:15-18;
[0026] Among them, the stirring speed is 550r / min;
[0027] The first mixed liquid is added into the reactor, and then an inert gas is introduced into the reactor to exhaust the air in the reactor;
[0028] Add ammonium fluoride to the reaction kettle, continue stirring for 30 minutes, adjust the temperature to 200°C, keep stirring for 24 hours, cool to room temperature, stand for 20 hours, filter, wash, vacuum dry, crush, and sieve to obtain a modified enhancer;
[0029] Wherein, the mixing ratio of ammonium fluoride to the first mixed solution is 1-2g:120mL;
[0030] The speed of heat preservation and stirring is 800r / min;
[0031] Wherein, washing is performed by using deionized water;
[0032] The vacuum drying temperature is 60°C;
[0033] The vacuum drying time was 10 hours;
[0034] The sieve mesh number is 350 mesh.
[0035] As a further technical solution: the inert gas is nitrogen or neon.
[0036] As a further technical solution: the micro-arc oxidation treatment is:
[0037] First, the bottom cover of the aerosol can is sanded to 1200# with sandpaper, then cleaned with deionized water at 50°C for 10 minutes, and then dried to constant weight;
[0038] Among them, the power supply used for micro-arc oxidation treatment in the present invention is a 30A300V bidirectional pulse power supply;
[0039] The micro-arc oxidation treatment was carried out in a constant voltage mode of 450V;
[0040] The frequency during micro-arc oxidation treatment is 650Hz;
[0041] The duty cycle during micro-arc oxidation treatment is 15-18%.
[0042] As a further technical solution: the micro-arc oxidation treatment time is 10-12 minutes.
[0043] Beneficial effects:
[0044] The aerosol can bottom cover material prepared by the present invention has strong strength performance and excellent corrosion resistance, and can be applied to aerosol can products in most fields.
[0045] The present invention significantly adjusts the composition of the aerosol can bottom cover material, especially a certain ratio of each metal component, so that it can produce a synergistic promotion effect and significantly improve the strength performance of the aerosol can bottom cover material.
[0046] The present invention further improves the strength of the bottom cover material of the aerosol can by adding zinc and titanium in the same proportion. Titanium and aluminum can form Al2O3, which is easy to precipitate. 3Ti phase, this compound can effectively strengthen the aluminum matrix, thereby improving the strength and rigidity of the aluminum alloy, and the introduction of zinc can further enhance its performance, significantly improving the mechanical properties of the aerosol can bottom cover material.
[0047] Through the coordinated effect of zinc and titanium, the microstructure of the bottom cover material of the aerosol can can be stably improved, thereby improving the corrosion resistance of the bottom cover material of the aerosol can, and being able to cope with the erosion of a variety of chemical products, so that the aerosol can can be loaded with a variety of chemical products.
[0048] The combination of titanium and zinc can also improve the processing performance of the aerosol can bottom cover material, especially for the manufacture of the aerosol can bottom cover, by reducing the thermal deformation temperature of the material and improving the fluidity of the material during the hot pressing process, making the aerosol can bottom cover material easier to process and form.
[0049] By performing micro-arc oxidation treatment on the bottom cover material of the aerosol can, the hardness of the surface of the bottom cover material of the aerosol can is greatly improved after the micro-arc oxidation treatment under the action of the electrolyte prepared by the present invention.
[0050] Micro-arc oxidation can form a dense protective film on the surface of the aerosol can bottom cover material, which greatly improves the corrosion resistance of the aerosol can bottom cover material.
[0051] At the same time, the aerosol can bottom cover material after micro-arc oxidation treatment also has good insulation and heat shock resistance, further broadening the application field of aerosol can bottom cover materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 It is a bar graph of stress corrosion index of each test group. DETAILED DESCRIPTION
[0053] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] Example 1
[0055] A high-strength aerosol can bottom cover material, comprising the following components by mass fraction:
[0056] Si 6.5%, Mg 0.22%, Cu 0.1%, Zn 0.5%, Ti 0.5%, Ni 0.08%, Fe 0.06%, Pb 0.003%, Sn 0.003%, the balance is Al;
[0057] The high-strength aerosol can bottom cover material is extruded once to form an upwardly convex curved surface as the aerosol can bottom cover;
[0058] The high-strength aerosol can bottom cover material is subjected to micro-arc oxidation treatment; the electrolyte components used in the micro-arc oxidation treatment include:
[0059] 1.0 g / L of modified enhancer, 10 g / L of sodium silicate, 10 g / L of sodium phosphate, 1 g / L of sodium metavanadate, 0.1 g / L of potassium titanium oxalate, and the rest is water; the mixing mass ratio of sodium metavanadate and potassium titanium oxalate is 10:1; the preparation method of the modified enhancer is:
[0060] First, add the complexing agent to the nitric acid solution, adjust the temperature to 40°C, and stir for 30 minutes to obtain a first mixed solution;
[0061] Wherein, the complexing agent is aminocarboxylic acid;
[0062] Among them, the mass concentration of nitric acid solution is 0.35mol / L;
[0063] The mass ratio of the complexing agent to the nitric acid solution is 1:15;
[0064] Among them, the stirring speed is 550r / min;
[0065] Add the first mixed liquid into the reactor, then introduce nitrogen or neon into the reactor to exhaust the air in the reactor;
[0066] Add ammonium fluoride to the reaction kettle, continue stirring for 30 minutes, adjust the temperature to 200°C, keep stirring for 24 hours, cool to room temperature, stand for 20 hours, filter, wash, vacuum dry, crush, and sieve through 350 mesh to obtain a modified enhancer;
[0067] Wherein, the mixing ratio of ammonium fluoride to the first mixed solution is 1 g:120 mL;
[0068] The speed of heat preservation and stirring is 800r / min;
[0069] Wherein, washing is performed by using deionized water;
[0070] The vacuum drying temperature is 60°C;
[0071] The vacuum drying time was 10 hours;
[0072] Micro-arc oxidation treatment is:
[0073] First, the bottom cover of the aerosol can is sanded to 1200# with sandpaper, then cleaned with deionized water at 50°C for 10 minutes, and then dried to constant weight;
[0074] Among them, the power supply used for micro-arc oxidation treatment in the present invention is a 30A300V bidirectional pulse power supply;
[0075] The micro-arc oxidation treatment was carried out in a constant voltage mode of 450V;
[0076] The frequency during micro-arc oxidation treatment is 650Hz;
[0077] The duty cycle during the micro-arc oxidation treatment is 15%; the micro-arc oxidation treatment time is 10 minutes.
[0078] Example 2
[0079] A high-strength aerosol can bottom cover material, comprising the following components by mass fraction:
[0080] Si 6.8%, Mg 0.23%, Cu 0.12%, Zn 0.8%, Ti 0.8%, Ni 0.05%, Fe 0.03%, Pb 0.003%, Sn 0.002%, the balance is Al;
[0081] The high-strength aerosol can bottom cover material is extruded once to form an upwardly convex curved surface as the aerosol can bottom cover;
[0082] The high-strength aerosol can bottom cover material is subjected to micro-arc oxidation treatment; the electrolyte components used in the micro-arc oxidation treatment include:
[0083] 1.2 g / L of modified enhancer, 13 g / L of sodium silicate, 15 g / L of sodium phosphate, 1.2 g / L of sodium metavanadate, 0.15 g / L of potassium titanium oxalate, and the rest is water; the mixing mass ratio of sodium metavanadate and potassium titanium oxalate is 10:1; the preparation method of the modified enhancer is:
[0084] First, add the complexing agent to the nitric acid solution, adjust the temperature to 40°C, and stir for 30 minutes to obtain a first mixed solution;
[0085] Wherein, the complexing agent is aminocarboxylic acid;
[0086] Among them, the mass concentration of nitric acid solution is 0.35mol / L;
[0087] The mass ratio of the complexing agent to the nitric acid solution is 1:16;
[0088] Among them, the stirring speed is 550r / min;
[0089] Add the first mixed liquid into the reactor, then introduce nitrogen or neon into the reactor to exhaust the air in the reactor;
[0090] Add ammonium fluoride to the reaction kettle, continue stirring for 30 minutes, adjust the temperature to 200°C, keep stirring for 24 hours, cool to room temperature, stand for 20 hours, filter, wash, vacuum dry, crush, and sieve through 350 mesh to obtain a modified enhancer;
[0091] Wherein, the mixing ratio of ammonium fluoride to the first mixed solution is 1.5 g:120 mL;
[0092] The speed of heat preservation and stirring is 800r / min;
[0093] Wherein, washing is performed by using deionized water;
[0094] The vacuum drying temperature is 60°C;
[0095] The vacuum drying time was 10 hours;
[0096] Micro-arc oxidation treatment is:
[0097] First, the bottom cover of the aerosol can is sanded to 1200# with sandpaper, then cleaned with deionized water at 50°C for 10 minutes, and then dried to constant weight;
[0098] Among them, the power supply used for micro-arc oxidation treatment in the present invention is a 30A300V bidirectional pulse power supply;
[0099] The micro-arc oxidation treatment was carried out in a constant voltage mode of 450V;
[0100] The frequency during micro-arc oxidation treatment is 650Hz;
[0101] The duty cycle during the micro-arc oxidation treatment is 16%; the micro-arc oxidation treatment time is 11 minutes.
[0102] Example 3
[0103] A high-strength aerosol can bottom cover material, comprising the following components by mass fraction:
[0104] Si 6.9%, Mg 0.28%, Cu 0.16%, Zn 0.7%, Ti 0.7%, Ni 0.05%, Fe 0.02%, Pb 0.002%, Sn 0.001%, the balance is Al;
[0105] The high-strength aerosol can bottom cover material is extruded once to form an upwardly convex curved surface as the aerosol can bottom cover;
[0106] The high-strength aerosol can bottom cover material is subjected to micro-arc oxidation treatment; the electrolyte components used in the micro-arc oxidation treatment include:
[0107] 1.3 g / L of modified enhancer, 15 g / L of sodium silicate, 12 g / L of sodium phosphate, 1.5 g / L of sodium metavanadate, 0.18 g / L of potassium titanium oxalate, and the rest is water; the mixing mass ratio of sodium metavanadate and potassium titanium oxalate is 10:1; the preparation method of the modified enhancer is:
[0108] First, add the complexing agent to the nitric acid solution, adjust the temperature to 40°C, and stir for 30 minutes to obtain a first mixed solution;
[0109] Wherein, the complexing agent is aminocarboxylic acid;
[0110] Among them, the mass concentration of nitric acid solution is 0.35mol / L;
[0111] The mass ratio of the complexing agent to the nitric acid solution is 1:16;
[0112] Among them, the stirring speed is 550r / min;
[0113] Add the first mixed liquid into the reactor, then introduce nitrogen or neon into the reactor to exhaust the air in the reactor;
[0114] Add ammonium fluoride to the reaction kettle, continue stirring for 30 minutes, adjust the temperature to 200°C, keep stirring for 24 hours, cool to room temperature, stand for 20 hours, filter, wash, vacuum dry, crush, and sieve through 350 mesh to obtain a modified enhancer;
[0115] Wherein, the mixing ratio of ammonium fluoride to the first mixed solution is 1.5 g:120 mL;
[0116] The speed of heat preservation and stirring is 800r / min;
[0117] Wherein, washing is performed by using deionized water;
[0118] The vacuum drying temperature is 60°C;
[0119] The vacuum drying time was 10 hours;
[0120] Micro-arc oxidation treatment is:
[0121] First, the bottom cover of the aerosol can is sanded to 1200# with sandpaper, then cleaned with deionized water at 50°C for 10 minutes, and then dried to constant weight;
[0122] Among them, the power supply used for micro-arc oxidation treatment in the present invention is a 30A300V bidirectional pulse power supply;
[0123] The micro-arc oxidation treatment was carried out in a constant voltage mode of 450V;
[0124] The frequency during micro-arc oxidation treatment is 650Hz;
[0125] The duty cycle during the micro-arc oxidation treatment is 16%; the micro-arc oxidation treatment time is 10 minutes.
[0126] Example 4
[0127] A high-strength aerosol can bottom cover material, comprising the following components by mass fraction:
[0128] Si 7.0%, Mg 0.24%, Cu 0.15%, Zn 0.8%, Ti 0.8%, Ni 0.06%, Fe 0.04%, Pb 0.001%, Sn 0.001%, the balance is Al;
[0129] The high-strength aerosol can bottom cover material is extruded once to form an upwardly convex curved surface as the aerosol can bottom cover;
[0130] The high-strength aerosol can bottom cover material is subjected to micro-arc oxidation treatment; the electrolyte components used in the micro-arc oxidation treatment include:
[0131] 1.2 g / L of modified enhancer, 12 g / L of sodium silicate, 13 g / L of sodium phosphate, 1.5 g / L of sodium metavanadate, 0.15 g / L of potassium titanium oxalate, and the rest is water; the mixing mass ratio of sodium metavanadate and potassium titanium oxalate is 10:1; the preparation method of the modified enhancer is:
[0132] First, add the complexing agent to the nitric acid solution, adjust the temperature to 40°C, and stir for 30 minutes to obtain a first mixed solution;
[0133] Wherein, the complexing agent is aminocarboxylic acid;
[0134] Among them, the mass concentration of nitric acid solution is 0.35mol / L;
[0135] The mass ratio of the complexing agent to the nitric acid solution is 1:17;
[0136] Among them, the stirring speed is 550r / min;
[0137] Add the first mixed liquid into the reactor, then introduce nitrogen or neon into the reactor to exhaust the air in the reactor;
[0138] Add ammonium fluoride to the reaction kettle, continue stirring for 30 minutes, adjust the temperature to 200°C, keep stirring for 24 hours, cool to room temperature, stand for 20 hours, filter, wash, vacuum dry, crush, and sieve through 350 mesh to obtain a modified enhancer;
[0139] Wherein, the mixing ratio of ammonium fluoride to the first mixed solution is 1.5 g:120 mL;
[0140] The speed of heat preservation and stirring is 800r / min;
[0141] Wherein, washing is performed by using deionized water;
[0142] The vacuum drying temperature is 60°C;
[0143] The vacuum drying time was 10 hours;
[0144] Micro-arc oxidation treatment is:
[0145] First, the bottom cover of the aerosol can is sanded to 1200# with sandpaper, then cleaned with deionized water at 50°C for 10 minutes, and then dried to constant weight;
[0146] Among them, the power supply used for micro-arc oxidation treatment in the present invention is a 30A300V bidirectional pulse power supply;
[0147] The micro-arc oxidation treatment was carried out in a constant voltage mode of 450V;
[0148] The frequency during micro-arc oxidation treatment is 650Hz;
[0149] The duty cycle during the micro-arc oxidation treatment is 16%; the micro-arc oxidation treatment time is 11 minutes.
[0150] Example 5
[0151] A high-strength aerosol can bottom cover material, comprising the following components by mass fraction:
[0152] Si7.1%, Mg0.30%, Cu0.2%, Zn0.1%, Ti0.1%, Ni0.05%, Fe0.03%, Pb0.003%, Sn0.003%, the balance is Al;
[0153] The high-strength aerosol can bottom cover material is extruded once to form an upwardly convex curved surface as the aerosol can bottom cover;
[0154] The high-strength aerosol can bottom cover material is subjected to micro-arc oxidation treatment; the electrolyte components used in the micro-arc oxidation treatment include:
[0155] 1.5 g / L of modified enhancer, 16 g / L of sodium silicate, 16 g / L of sodium phosphate, 2 g / L of sodium metavanadate, 0.2 g / L of potassium titanium oxalate, and the rest is water; the mixing mass ratio of sodium metavanadate and potassium titanium oxalate is 10:1; the preparation method of the modified enhancer is:
[0156] First, add the complexing agent to the nitric acid solution, adjust the temperature to 40°C, and stir for 30 minutes to obtain a first mixed solution;
[0157] Wherein, the complexing agent is aminocarboxylic acid;
[0158] Among them, the mass concentration of nitric acid solution is 0.35mol / L;
[0159] The mass ratio of the complexing agent to the nitric acid solution is 1:18;
[0160] Among them, the stirring speed is 550r / min;
[0161] Add the first mixed liquid into the reactor, then introduce nitrogen or neon into the reactor to exhaust the air in the reactor;
[0162] Add ammonium fluoride to the reaction kettle, continue stirring for 30 minutes, adjust the temperature to 200°C, keep stirring for 24 hours, cool to room temperature, stand for 20 hours, filter, wash, vacuum dry, crush, and sieve through 350 mesh to obtain a modified enhancer;
[0163] Wherein, the mixing ratio of ammonium fluoride to the first mixed solution is 2g:120mL;
[0164] The speed of heat preservation and stirring is 800r / min;
[0165] Wherein, washing is performed by using deionized water;
[0166] The vacuum drying temperature is 60°C;
[0167] The vacuum drying time was 10 hours;
[0168] Micro-arc oxidation treatment is:
[0169] First, the bottom cover of the aerosol can is sanded to 1200# with sandpaper, then cleaned with deionized water at 50°C for 10 minutes, and then dried to constant weight;
[0170] Among them, the power supply used for micro-arc oxidation treatment in the present invention is a 30A300V bidirectional pulse power supply;
[0171] The micro-arc oxidation treatment was carried out in a constant voltage mode of 450V;
[0172] The frequency during micro-arc oxidation treatment is 650Hz;
[0173] The duty cycle during the micro-arc oxidation treatment is 18%; the micro-arc oxidation treatment time is 12 minutes.
[0174] Comparative Example 1:
[0175] Based on Example 1, the micro-arc oxidation treatment is not performed, and the other technical solutions remain unchanged.
[0176] Comparative Example 2:
[0177] Based on Example 1, no modifier is added to the electrolyte used in the micro-arc oxidation treatment, and the rest of the technical solutions remain unchanged.
[0178] test:
[0179] The surface of the bottom cover of the aerosol can obtained from the example material was observed:
[0180] Table 1
[0181]
[0182]
[0183] It can be seen from Table 1 that the surface of the aerosol can bottom cover material prepared by the present invention has a relatively complete protective film.
[0184] The tensile strength of the samples of the embodiment and the comparative example was tested at room temperature and pressure using a universal tensile testing machine (model WDW-100). The results are shown in Table 2:
[0185] Table 2
[0186] Tensile strength MPa Example 1 588 Example 2 581 Example 3 586 Example 4 588 Example 5 585 Comparative Example 1 543 Comparative Example 2 567
[0187] It can be seen from Table 2 that the aerosol can bottom cover material prepared by the present invention has higher strength performance.
[0188] The hardness of the samples of the embodiment and the comparative example was tested at room temperature using a hardness tester (Perrick 934-1 / 1S Barcol hardness tester), as shown in Table 3:
[0189] Table 3
[0190] Hardness HRC Example 1 178 Example 2 181 Example 3 175 Example 4 173 Example 5 177 Comparative Example 1 146 Comparative Example 2 158
[0191] It can be seen from Table 3 that the surface hardness of the aerosol can bottom cover material prepared by the present invention is greatly improved.
[0192] Corrosion test standard: GB / T15970.7-2000 Corrosion stress corrosion test of metals and alloys Part 7: Slow strain rate test:
[0193] The examples and comparative samples were tested:
[0194] Table 4
[0195] Stress corrosion index % Example 1 4 Example 2 3 Example 3 3 Example 4 5 Example 5 3 Comparative Example 1 14 Comparative Example 2 8
[0196] It can be seen from Table 4 that the aerosol can bottom cover material prepared by the present invention has excellent corrosion resistance.
[0197] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.
Claims
1. A high-strength aerosol can bottom cover material, characterized in that: The composition includes the following ingredients by mass fraction: Si6.5-7.1%, Mg0.22-0.30%, Cu0.1-0.2%, Zn0.5-0.1%, Ti0.5-0.1%, Ni≤0.1%, Fe≤0.1%, Pb≤0.003%, Sn≤0.003%, the balance is Al; The high-strength aerosol can bottom cover material is subjected to micro-arc oxidation treatment.
2. A high-strength aerosol can bottom cover material according to claim 1, characterized in that: The mass ratio of Zn to Ti is 1:
1.
3. A high-strength aerosol can bottom cover material according to claim 2, characterized in that: The Ni mass fraction is greater than the Fe mass fraction.
4. The high-strength aerosol can bottom cover material according to claim 1, characterized in that: The electrolyte components used in the micro-arc oxidation treatment include: Modifier and enhancer 1.0-1.5g / L, sodium silicate 10-16g / L, sodium phosphate 10-16g / L, sodium metavanadate 1-2g / L, potassium titanium oxalate 0.1-0.2g / L, and the rest is water.
5. The high-strength aerosol can bottom cover material according to claim 4, characterized in that: The mixing mass ratio of the sodium metavanadate and potassium titanium oxalate is 10:
1.
6. The high-strength aerosol can bottom cover material according to claim 1, characterized in that: The preparation method of the modified reinforcing agent is: First, add the complexing agent to the nitric acid solution, adjust the temperature to 40°C, and stir for 30 minutes to obtain a first mixed solution; Wherein, the complexing agent is aminocarboxylic acid; Among them, the mass concentration of nitric acid solution is 0.35mol / L; The mass ratio of the complexing agent to the nitric acid solution is 1:15-18; Among them, the stirring speed is 550r / min; Adding the first mixed liquid into the reactor, then introducing inert gas into the reactor and exhausting the air in the reactor; Add ammonium fluoride to the reaction kettle, continue stirring for 30 minutes, adjust the temperature to 200°C, keep stirring for 24 hours, cool to room temperature, stand for 20 hours, filter, wash, vacuum dry, crush, and sieve to obtain a modified enhancer; Wherein, the mixing ratio of ammonium fluoride to the first mixed solution is 1-2g:120mL; The speed of heat preservation and stirring is 800r / min; Wherein, washing is performed by using deionized water; The vacuum drying temperature is 60°C; The vacuum drying time was 10 hours; The sieve mesh number is 350 mesh.
7. The high-strength aerosol can bottom cover material according to claim 6, characterized in that: The inert gas is nitrogen or neon.
8. The high-strength aerosol can bottom cover material according to claim 1, characterized in that: The micro-arc oxidation treatment is: First, the bottom cover of the aerosol can is sanded to 1200# with sandpaper, then cleaned with deionized water at 50°C for 10 minutes, and then dried to constant weight; Among them, the power supply used for micro-arc oxidation treatment in the present invention is a 30A300V bidirectional pulse power supply; The micro-arc oxidation treatment was carried out in a constant voltage mode of 450V; The frequency during micro-arc oxidation treatment is 650Hz; The duty cycle during micro-arc oxidation treatment is 15-18%.
9. The high-strength aerosol can bottom cover material according to claim 8, characterized in that: The micro-arc oxidation treatment time is 10-12 minutes.